2019
DOI: 10.1017/s0033291719000023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental illness in primary care and its association with deprivation and social fragmentation at the small-area level in England

Abstract: BackgroundWe aimed to spatially describe mental illness prevalence in England at small-area geographical level, as measured by prevalence of depression, severe mental illness (SMI) and antidepressant prescription volume in primary care records, and how much of their variation was explained by deprivation, social fragmentation and sociodemographic characteristics.MethodsInformation on prevalence of depression and SMI was obtained from the Quality and Outcomes Framework (QOF) administrative dataset for 2015/16 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…A previous study reported that for people of all ages in England, the prevalence of antidepressant prescriptions was lowest in London and highest in the North East of England [24]. We also found the lowest incident prescription rates in London; however, the North East was the next lowest area for adolescents.…”
Section: Comparison With Other Studiessupporting
confidence: 66%
See 3 more Smart Citations
“…A previous study reported that for people of all ages in England, the prevalence of antidepressant prescriptions was lowest in London and highest in the North East of England [24]. We also found the lowest incident prescription rates in London; however, the North East was the next lowest area for adolescents.…”
Section: Comparison With Other Studiessupporting
confidence: 66%
“…Our study has good face validity because we found similar trends to those published elsewhere. For example, we found that after adjustment for GP practice clustering and region, CYP living in more deprived areas are more likely to receive antidepressant prescriptions compared with those in the less deprived areas, which has previously been shown for children and adolescents [15,16] and adults [24] in the UK. Although the unadjusted results showed lower antidepressant prescribing in adolescents living in the most deprived quintile (S2 Fig), this was due to the lower prescribing and large proportion of people living in the most deprived quintile in London.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
See 2 more Smart Citations
“…When deriving the K10 score, items 3 and 6 were recoded to "none of the time" if the response to the previous question was also "none of the time", as per the standard interpretation [20]. Using previous Australian thresholds for likelihood of a clinical case, K10 scores were categorised into low (10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and high (26-50) groups [21].…”
Section: Psychological Distressmentioning
confidence: 99%